Silence fallen - Briggs, Patricia (Briggs, Patricia. Mercy Thompson novels., 2017)
"A new hardcover in the acclaimed Mercy Thompson series--from the #1 New York Times bestselling author of Fire Touched. Attacked and abducted in her home territory, Mercy finds herself in the clutches of the most powerful vampire in the world, taken as a weapon to use against alpha werewolf Adam and the ruler of the Tri-Cities vampires. In coyote form, Mercy escapes--only to find herself without money, without clothing, and alone in the heart of Europe... Unable to contact Adam and the rest of the pack, Mercy has allies to find and enemies to fight, and she needs to figure out which is which. Ancient powers stir, and Mercy must be her agile best to avoid causing a war between vampires and werewolves, and between werewolves and werewolves. And in the heart of the ancient city of Prague, old ghosts rise..."--